Variabilité des formes terminologiques (sur l’exemple des termes français et polonais du régime supplémentaire de retraite) - Kozar, Liliana (Neophilologica, 2017)
Even a cursory look at the specialized texts functioning within a given field of knowledge leads us to state that the terminology used in them is not homogeneous. That heterogeneity manifests itself at different levels and implies at least a few linguistic phenomena. One of them is variability or modifiability of some terminological forms appointed to designate one and the same concept. The subject of the analysis undertaken in this paper is the French and Polish terminology in the field of individual retirement plans, while its purpose is a quantitative and qualitative analysis of variant terms occurring in the texts.